MON-132 DKA Accompanied with Concomitant Hypertriglyceridemia-Induced Acute Pancreatitis as Initial Presentation of Ketosis-Prone Diabetes - Monsour, Elio (J Endocr Soc, 2019)
Background: Ketosis-prone diabetes (KPD) or Flatbush diabetes has been reported as an initial presentation of DKA; There are, however, limited presentations of this phenomenon with co-existing hypertriglyceridemia-induced acute pancreatitis with normal serum lipase. Clinical Case: A 29-year-old African-American man presented with a 2-week history of epigastric pain, nausea, and vomiting. Associated symptoms included nocturnal polyuria and polydipsia and 10 lbs unintentional wt loss. He had no previous known history of diabetes; no current use of medications and past medical history was significant for medically-complicated obesity. Vital signs were remarkable for BMI of 43.3. Physical exam was mostly unrevealing except for decreased skin turgor and dry oral mucosa. Baseline chemistry and serology showed HbA1c of 11.1%, blood glucose of 910 mg/dl, serum Bicarbonate 16 mg/dl, Potassium 5.7 mmol/K, Anion Gap 19 mEq/L, with positive serum and urinary ketones. Serum lipase of 100 U/L (0-160 U/L), triglycerides of 1575 mg/dL (<150 mg/dL). Additional work-up revealed fasting C-peptide level of 2.09 (1.1−4.4 ng/mL), GAD-65 Ab titers: <5.0 U/mL (0.0−5.0 units/mL), and negative ICA (<1.1). CT Abdomen and Pelvis was remarkable for focal pancreatitis with thickening in the peripancreatic space. Biochemical testing and clinical picture were consistent with ketosis-prone T2DM. Conclusions: KPD is a different subset of diabetes, characterized by unprovoked ketosis or new-onset DKA. However, patients lack the standard phenotypes of T1DM or LADA. The underlying pathophysiology of KPD is thought to be due to β-islet cell dysfunction. Phenotypes of KPD may be further broken down via the presence or absence of β-islet cell autoantibodies, as well as long-term β-cell reserve. In our case described, the patient had negative autoantibodies and residual β-cell function, which is classified as KPD subtype A−β+. Furthermore, free fatty acidbreakdown by pancreatic lipases results in hypertriglyceridemia or lipotoxicity resulting in acute pancreatitis. Initially, management is the same as for those with T1DM with ketoacidosis, and all patients should be maintained on insulin until C-peptide levels can then be retested in 2 to 10 weeks to assess trajectory and determine transient vs. long-term insulin requirements and dependency. References: -Navina S, Acharya C, DeLany JP, et al. Lipotoxicity causes multisystem organ failure and exacerbates acute pancreatitis in obesity. Sci Transl Med. 2011;3(107):107ra110. -Balasubramanyam A, Nalini R, Hampe CS, Maldonado M. Syndromes of ketosis-prone diabetes mellitus. Endocr Rev. 2008;29(3):292-302. -Maldonado, M.R., Otiniano, M.E., Cheema, F. , Rodriguez, L. and Balasubramanyam, A. (2005), Factors associated with insulin discontinuation in subjects with ketosis‐prone diabetes but preserved β‐cell function. Diabetic Medicine, 22: 1744-1750.